FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN HYPEREMESIS GRAVIDARUM PADA IBU HAMIL TRIMESTER I - Butu, Yosepina Otma; Rottie, Julia; Bataha, Yolanda (JURNAL KEPERAWATAN, 2019)
Abstract: Hyperemesis gravidarum is a condition of excessive nausea and vomiting duringpregnancy. Thepurpose of this study is to knowsomefactor that associated with the incidenceof Hyperemesis Gravidarum in first trimester pregnant women atPuskesmasBahu Manado,and in this study, three factors were taken,There are age, parity status, and employment.Themethod of this study uses a quantitative method with a cross sectional design. Thesample of this study was amounted to 30 people using total sampling method. The Resultsofthis study, using the chi-square test, obtained the value of Asymp. Sig on the age variable is0.964; on the parity variable 0.092; and the employment variable is 0.374. These resultsindicate that this value is> 0.05, which means there is significant relationship between age,parity and employment with the incidence of hyperemesis gravidarum. Conclusion from theresearch conducted based on the relationship of factor related to the incidence ofhyperemesis gravidarum,general,parity,and work there is a meaningful relationship.Keywords: Hyperemesis GravidarumAbstrak: Hyperemesis gravidarum adalah keadaan mual dan muntah berlebihan selama masakehamilan. Tujuan studi untuk melihat faktor-faktor yang berhubungan dengan kejadianHyperemesis Gravidarum pada ibu hamil trimester I di Puskesmas Bahu Manado, dan dalampenelitian ini, diambil 3 faktor, yaitu umur, status paritas, dan pekerjaan ibu. Metode studi inimenggunakan metode kuantitatif dengan desain cross sectional. Sampel studi ini berjumlah30 orang dengan menggunakan metode pengambilan sampel total sampling.Hasil daripenelitian ini, dengan menggunakan uji chi – square didapatkan bahwa nilai Asymp.Sig padavariabel umur adalah 0,964; pada variabel paritas 0,092; dan pada variabel pekerjaan sebesar0,374. Hasil ini menunjukkan bahwa Nilai ini > 0,05, yang berarti ada hubungan yangbermakna antara umur, paritas dan pekerjaan dengan kejadian hyperemesis gravidarum.Simpulan dari penelitian yang dilakukan berdasarkan hubungan faktor-faktor yangberhubungan dengan kejadian hyperemesis garavidarum,Umur Paritas dan Pekerjaan adalahada hubungan yang bermakna.Kata kunci :Hyperemesis Gravidarum